The Service Quality Effect on Corporate Reputation, Customers Satisfaction, and Loyalty - Dwi Putranto Hadi; Rhian Indradewa (Journal of Multidisciplinary Academic, 2019)
The superiority of a service is depends on the uniqueness and quality service. The service must be specifically meet customer needs and desires because the service is felt and enjoyed directly by the customer will immediately get an assessment according to the expectations. This study discusses a quality of forklift rental services. Here, a service quality variables as forming company reputation, customer satisfaction, and customer loyalty. Using causality and quantitative analysis models. All the data collected through the distribution of questionnaires to 250 forklift customers rental companies over (PT. Kianis Pratama, Indonesia) uses SEM analysis. The purpose in this study to determine service quality effect over corporate reputation, customer satisfaction, and loyalty, respectively. The results shows that a good service quality would increase the corporate reputation and customer satisfaction, a good corporate reputation would increase customer loyalty and high customer satisfaction would increase customer loyalty. It means that the better of corporate reputation has, higher of customer satisfaction and loyalty will be increase customer satisfaction in the PT. Kianis Pratama